Squamous cell carcinoma of the cecum developing in a patient with long-standing ulcerative colitis and a coexistent carcinoid tumor in the appendix: A case report - Saqib Ahmad; Nicholas Watson; Kiran Shamim; Achyuth Menon; Khorrum Abdullah (Turkish Journal of Gastroenterology, 2019)
Squamous cell carcinoma (SCC) of the colon is a rare tumor that accounts for 0.1%–0.2% of colonic malignancies. However, pure SCC of the cecum is extremely rare. Although SCC of the colon is a rare complication of idiopathic inflammatory bowel disease (IBD), SCC of the cecum in the context of IBD has not been previously reported in the English literature. We report a case of the coexistence of SCC of the cecum and a carcinoid tumor in a 46-year-old female with long-standing pan-ulcerative colitis.